2019
DOI: 10.3390/molecules24173180
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Molecular Docking Analysis of Flavonoid Derivatives as Potential Telomerase Inhibitors

Abstract: Based on the structural scaffolds of natural products, two series of flavonoid derivatives, for a total of twelve compounds, were designed and synthesized as potential human telomerase inhibitors. Using a modified TRAP-PCR assay, compound 5c exhibited the most potent inhibitory activity against human telomerase with an IC50 value of less than 50 μM. In vitro, the results demonstrated that compound 5c had potent anticancer activity against five classes of tumor cell lines. The molecular docking and molecular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The spheres in blue, red, and green colors indicate the high toxicity, low toxicity, and no toxicity, respectively. After calculations, only 25 S1) were found to have no mutagenicity, tumorigenicity, irritant, and reproductive effect, in good agreement with the reported biogical activities [81,82,[84][85][86]. Therefore, these molecules were then subjected to binding affinity prediction against the ATPase domain of GyrB using molecular docking analysis.…”
Section: Toxicity Assessmentsupporting
confidence: 66%
“…The spheres in blue, red, and green colors indicate the high toxicity, low toxicity, and no toxicity, respectively. After calculations, only 25 S1) were found to have no mutagenicity, tumorigenicity, irritant, and reproductive effect, in good agreement with the reported biogical activities [81,82,[84][85][86]. Therefore, these molecules were then subjected to binding affinity prediction against the ATPase domain of GyrB using molecular docking analysis.…”
Section: Toxicity Assessmentsupporting
confidence: 66%
“…Considering that telomerase is widely expressed in human tumors and tumor-derived cell lines, whereas in the normal stem cell this enzyme activity is proportionally low, the inhibition of this enzyme is a strategy for anticancer drug discovery [ 80 ]. Fan et al (2019) reported the synthesis and telomerase inhibitory potential of 1,2,3-linked flavonol-glycosyl hybrid 40 ( Figure 14 ) [ 81 ]. The synthesis was performed by Click Chemistry, with previously obtained O -propargylated flavonol and glycosyl azide.…”
Section: 123-triazole-linked Flavonoid Hybrids With Antitumor Activitymentioning
confidence: 99%
“…Interestingly, 40 revealed no cytotoxic effect against two normal cells (Hacat and human bronchial epithelial BEAS-2B), with IC 50 values > 200 μM, showing selectivity for cancer cells. Molecular docking studies and molecular dynamics analyses allowed us to conclude that 40 has similar interactions with telomerase to those observed for BIBR1532, a highly specific inhibitor of this enzyme [ 81 ].…”
Section: 123-triazole-linked Flavonoid Hybrids With Antitumor Activitymentioning
confidence: 99%
“…Several other compounds designed using in silico approaches have been tested as potential inhibitors of the catalytic subunit of telomerase such as benzylidene-hydrazone analogs [22], dihydropyrazole [23][24][25][26][27][28][29], dibenzopyrroles [30], flavone pyridines [31], 1,3,4-oxadiazole derivatives [32][33][34][35][36], pyrazole-5-carboxamides and pyrazole-pyrimidines [37], spiroketals [37], celastrol derivatives [38], myricetin derivatives [39], indolyl-2'-deoxynucleotide analogs [40], flavonoid derivatives [41], and chrolactomycin derivatives [42]. Other classes of compounds developed as telomerase inhibitors are reported in two recent reviews [43,44].…”
Section: Introductionmentioning
confidence: 99%